Global comparison of chromosome X genes of pulmonary telocytes with mesenchymal stem cells, fibroblasts, alveolar type II cells, airway epithelial cells, and lymphocytes. Issue 1 (December 2015) - Zhu, Yichun; Zheng, Minghuan; Song, Dongli; Ye, Ling; Wang, Xiangdong
Abstract Background Telocytes (TCs) are suggested as a new type of interstitial cells with specific telopodes. Our previous study evidenced that TCs differed from fibroblasts and stem cells at the aspect of gene expression profiles. The present study aims to search the characters and patterns of chromosome X genes of TC-specific or TC-dominated gene profiles and fingerprints, investigate the network of principle genes, and explore potential functional association. Methods We compared gene expression profiles in chromosome X of pulmonary TCs with mesenchymal stem cells (MSC), fibroblasts (Fb), alveolar type II cells (ATII), airway basal cells (ABC), proximal airway cells (PAC), CD8+ T cells come from bronchial lymph nodes (T-BL), or CD8+ T cells from lungs (T-L) by global analyses, and selected the genes which were consistently up or down regulated (>1 fold) in TCs compared to other cells as TC-specific genes. The functional and characteristic networks were identified and compared by bioinformatics tools. Results We selected 31 chromosome X genes as the TC-specific or dominated genes, among which 8 up-regulated (Flna, Msn, Cfp, Col4a5, Mum1l1, Rnf128, Syn1, and Srpx2) and 23 down-regulated (Abcb7, Atf1, Ddx26b, Drp2, Fam122b, Gyk, Irak1, Lamp2, Mecp2, Ndufb11, Ogt, Pdha1, Pola1, Rab9, Rbmx2, Rhox9, Thoc2, Vbp1, Dkc1, Nkrf, Piga, Tmlhe and Tsr2), as compared with other cells. Conclusions Our data suggested that gene expressions of chromosome X in TCs are different with those in other cells in the lung tissue. According to the selected TC-specific genes, we infer that pulmonary TCs function as modulators which may enhance cellular growth and migration, resist senescence, protect cells from external stress, regulate immune responses, participate in tissue remodeling and repair, regulate neural function, and promote vessel formation.